2009
DOI: 10.1007/s10943-009-9242-1
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Health, and Psychological Well-Being

Abstract: This study compares the effects of religiosity on health and well-being, controlling for work and family. With 2006 GSS data, we assess the effects of religiosity on health and well-being, net of job satisfaction, marital happiness, and financial status. The results indicate that people who identify as religious tend to report better health and happiness, regardless of religious affiliation, religious activities, work and family, social support, or financial status. People with liberal religious beliefs tend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(109 citation statements)
references
References 48 publications
8
94
4
3
Order By: Relevance
“…The link between faith and resilience was demonstrated in our participants' narratives on numerous occasions while speaking about experiences of loss, illness, and separation from the family-for a long or short time and various reasons. This link has also been shown by several other studies [53][54][55] which underline the positive role of faith in coping with life events and stressors. It was clear from the participants' accounts that faith provided them with a framework of meaning and helped them to make sense of their situation regardless of the size, scale, or level of difficulty they faced in their everyday lives:…”
Section: Dealing With Separation and Partingsupporting
confidence: 80%
“…The link between faith and resilience was demonstrated in our participants' narratives on numerous occasions while speaking about experiences of loss, illness, and separation from the family-for a long or short time and various reasons. This link has also been shown by several other studies [53][54][55] which underline the positive role of faith in coping with life events and stressors. It was clear from the participants' accounts that faith provided them with a framework of meaning and helped them to make sense of their situation regardless of the size, scale, or level of difficulty they faced in their everyday lives:…”
Section: Dealing With Separation and Partingsupporting
confidence: 80%
“…Similar findings were reported by Meraviglia (2004), he showed that higher meaning in life scores was associated with higher psychological well-being and lower symptom distress scores and also higher prayer scores were associated with higher psychological well-being scores. Green and Elliott (2009) believed that religious identity has positive association with physical health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Koenig et al (2000) have found out a significant positive relationship between religious orientation and well-being. Green and Elliott (2009) indicated that religious identity is positively associated with physical health and well-being whereas liberal religious beliefs are positively associated with physical health and negatively associated with happiness, and they also suggested that religious activities only improve health or well-being among people who identify as religious persons. In a study, Ardelt (2003) showed that purpose in life rather than extrinsic or intrinsic religious orientation was positively related to elders' subjective well-being and negatively associated with fear of death and death avoidance.…”
Section: Religiosity and Psychological Well-beingmentioning
confidence: 99%
“…Some of these variables included social competence (Holopainen, Lappalainen, Junttila, & Savolainen, 2012), self-respect, self-confidence (Sandhu, Singh, Tung, & Kundra, 2012), personality traits such as neuroticism, extroversion and openness (Kokko, Tolvanen & Pulkkinen, 2013), emotional intelligence (James, Bore, & Zito, 2012), social network (Park, Song, & Lee, 2014), optimism (Souri & Hasanirad, 2011), religion and religiousness (Green & Elliott, 2010;Unterrainer, Ladenhauf, Moazedi, Wallner-Liebmann, & Fink, 2010), employment, level of education, marriage, age and gender (Khumalo, Temane, & Wissing, 2012), and physical health (Shields & Price, 2005). In addition to these variables, the social support perceived from different sources was noticed to be efficient upon psychological well-being of individuals (Brough & Pears, 2004;Daniels & Guppy, 1997;Du, Li, Chi, Zhao, & Zhao, 2015;Silverstein, Chen, & Heller, 1996).…”
Section: Both Traditions Have Concretized Humanist Values In Increasimentioning
confidence: 99%